Critical Representation of Figures, Symbols, and Power in Political Communication: Bibliometric Analysis of Phenomenological Studies - Anida Kusuma Ning Ariati; Anang Sujoko (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This study aimed to examine the critical representation of figures, symbols, and power in political communication through a critical phenomenological approach combined with bibliometric analysis. It mapped research trends, key authors, dominant keywords, and citation networks that emerged in phenomenological studies of political communication during 2010–2025. Data were collected using Publish or Perish software and analyzed with Excel and VOSviewer to illustrate relationships among keywords, authors, and citations. The findings showed a significant increase in publications since 2021, with dominant themes including gender representation, populist figures, and the symbolism of power in digital media. The results also indicated that scholarly discourse in this field had become increasingly fragmented while simultaneously consolidating around certain clusters, particularly those related to communicative action, political narratives, and identity politics. The study concluded that combining bibliometric methods with critical phenomenology revealed the discursive landscape and representational biases in contemporary political communication. It further provided conceptual and methodological contributions to the development of political communication studies grounded in the critique of representation and symbolic experience.